(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper investigates the role of speaking activities in English language classrooms through a needs analysis questionnaire. The aim is to explore students’ preferences, needs, and challenges related to speaking tasks and to improve classroom activities accordingly. Speaking activities are essential for enhancing learners’ fluency, confidence, and interaction skills.